1993
DOI: 10.1002/chin.199339214
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Properties of 3,5‐Dibromo‐4‐oxo‐2,2,6,6‐ tetramethylpiperidin‐1‐oxyl.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the synthesis of 3,5-dibromo-4-oxo-2,2,6,6-tetramethylpiperidin-1-yl oxide, treatment of piperidinoxyl radical with formic acid followed by bromine afforded 75% dibromohydroxypiperidine. Oxidation of the latter with NaNO 2 afforded the desired compound . Khelevina et al studied the tetraazaporphine bromination .…”
Section: Bromination Reactionsmentioning
confidence: 79%
See 1 more Smart Citation
“…In the synthesis of 3,5-dibromo-4-oxo-2,2,6,6-tetramethylpiperidin-1-yl oxide, treatment of piperidinoxyl radical with formic acid followed by bromine afforded 75% dibromohydroxypiperidine. Oxidation of the latter with NaNO 2 afforded the desired compound . Khelevina et al studied the tetraazaporphine bromination .…”
Section: Bromination Reactionsmentioning
confidence: 79%
“…Oxidation of the latter with NaNO 2 afforded the desired compound. 434 Khelevina et al studied the tetraazaporphine bromination. 435 They found that a 1:1 mixture of bromine and tetraazaporphine formed a 1:1 bromine complex in acetic acid.…”
Section: Bromination Reactions 31 Bromination With Molecular Brominementioning
confidence: 99%